2019
DOI: 10.1029/2018jd029772
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mixed‐Phase Convective Clouds by a Binary Phase Information From the Passive Geostationary Instrument SEVIRI

Abstract: Between −37 and 0 °C, clouds are liquid, ice, or mixed phase. Nearly all retrieval algorithms for passive instruments provide binary phase information—ice or liquid—making it difficult to retrieve mixed‐phase cloud properties. Based on measurements from the geostationary space‐based instrument Spinning Enhanced Visible and InfraRed Imager (SEVIRI), we show that the retrieved ice crystal effective radius is smaller than the liquid droplet effective radius for 48% of 230 analyzed cloud thermodynamic phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 67 publications
(105 reference statements)
3
20
0
Order By: Relevance
“…In Figures 3e and 3f, we observe a decrease of r e at the phase transition as already described by Coopman et al (2019): The reason for this apparently unphysical feature is that the values of r e depend on the thermodynamic phase retrieved by the algorithm beforehand. Unfortunately, CLAAS‐2 does not consider mixed‐phase clouds that lead to a bias in cloud microphysical property retrievals.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…In Figures 3e and 3f, we observe a decrease of r e at the phase transition as already described by Coopman et al (2019): The reason for this apparently unphysical feature is that the values of r e depend on the thermodynamic phase retrieved by the algorithm beforehand. Unfortunately, CLAAS‐2 does not consider mixed‐phase clouds that lead to a bias in cloud microphysical property retrievals.…”
Section: Resultssupporting
confidence: 78%
“…Figures 5d, 5e, and 5f show the T g distribution for the two regimes of CAPE(t 0 ), reIcefalse(t0.3pt+.3pt2normalΔt), and reLiqfalse(t02normalΔt). We can notice that the lower and upper quartiles of reIcefalse(t0+2normalΔ t) and reLiqfalse(t02normalΔt) are similar, which can be surprising: We expect reIcefalse(t0+2normalΔt) to be larger than reLiqfalse(t02normalΔ t), but the similar values are an artifact around the phase transition already described by Coopman et al (2019) and explained earlier. Clouds with CAPE(t 0 ) less than 11 J/kg are associated with a median T g of −23.9°C and clouds with CAPE(t 0 ) greater than 476.5 J/kg are associated with a median T g of −17.2°C.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Several studies have shown that mixed-phase clouds occur irrespective of the season, can be found in diverse locations, and can be associated with various cloud types (Korolev et al, 2017). Observations of mixed-phase clouds include active (e.g., Zhang et al, 2010;Tan et al, 2014;Cesana & Storelvmo, 2017) and passive satellite (e.g., Coopman et al, 2019;Noh et al, 2019;Tan et al, 2019), airborne in situ (e.g., Korolev, 2008;Costa et al, 2017;Barrett et al, 2020), ground-based (e.g., Henneberger et al, 2013;Yu et al, 2014;Gierens et al, 2020) and aircraft-based remote sensing measurements (e.g., Wang et al, 2012;Plummer et al, 2014). In Tan et al (2014), in particular, mixed-phase clouds have been studied statistically in terms of supercooled cloud fraction, defined as the ratio of the in-cloud frequency of supercooled liquid pixels to the total frequency of supercooled liquid and ice pixels within 2 • latitude by 5 • longitude grid boxes, at several isotherms between -10 • C and -30 • C, distinguishing cases in the Northern Hemisphere (NH) and in the Southern Hemisphere (SH), as well as cases over ocean and over land.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that mixed‐phase clouds occur irrespective of the season, can be found in diverse locations, and can be associated with various cloud types (Korolev et al., 2017). Observations of mixed‐phase clouds include active (e.g., Cesana & Storelvmo, 2017; Tan et al., 2014; Zhang et al., 2010) and passive satellite (e.g., Coopman et al., 2019; Noh et al., 2019; Tan et al., 2019), airborne in situ (e.g., Barrett et al., 2020; Costa et al., 2017; Korolev, 2008), ground‐based (e.g., Gierens et al., 2020; Henneberger et al., 2013; Yu et al., 2014) and aircraft‐based remote sensing measurements (e.g., Plummer et al., 2014; Wang et al., 2012). In Tan et al.…”
Section: Introductionmentioning
confidence: 99%